Empowerment-based nutrition interventions on blood pressure: a randomized comparative effectiveness trial - Moreira-Rosário, André; Ismael, Shámila; Barreiros-Mota, Inês; Morais, Juliana; Rodrigues, Catarina; Castela, Inês; Mendes, Inês Curvelo; Soares, Maria Inês; da Costa, Luís Soares; Oliveira, Catarina Batista; Henriques, Tiago; Pinto, Patrícia; et al. (Frontiers in Public Health, 2023)
Introduction Empowerment lifestyle programs are needed to reduce the risk of hypertension. Our study compared the effectiveness of two empowerment-based approaches toward blood pressure (BP) reduction: salt reduction-specific program vs. healthy lifestyle general program. Methods Three hundred and eleven adults (median age of 44 years, IQR 34–54 years) were randomly assigned to a salt reduction (n = 147) or a healthy lifestyle program (n = 164). The outcome measures were urinary sodium (Na+) and potassium (K+) excretion, systolic (SBP) and diastolic (DBP) blood pressure, weight, and waist circumference. Results There were no significant differences in primary and secondary outcomes between the two program groups. When comparing each program to baseline, the program focused on salt reduction was effective in lowering BP following a 12-week intervention with a mean change of −2.5 mm Hg in SBP (95% CI, −4.1 to −0.8) and − 2.7 mm Hg in DBP (95% CI, −3.8 to −1.5) in the intention-to-treat (ITT) analysis. In the complete-case (CC) analysis, the mean change was −2.1 mm Hg in SBP (95% CI, −3.7 to −0.5) and − 2.3 mm Hg in DBP (95% CI, −3.4 to −1.1). This effect increases in subjects with high-normal BP or hypertension [SBP − 7.9 mm Hg (95% CI, −12.5 to −3.3); DBP − 7.3 mm Hg (95% CI, −10.2 to −4.4)]. The healthy lifestyle group also exhibited BP improvements after 12 weeks; however, the changes were less pronounced compared to the salt reduction group and were observed only for DBP [mean change of −1.5 mm Hg (95% CI, −2.6 to −0.4) in ITT analysis and − 1.4 mm Hg (95% CI, −2.4 to −0.3) in CC analysis, relative to baseline]. Overall, improvements in Na+/K+ ratio, weight, and Mediterranean diet adherence resulted in clinically significant SBP decreases. Importantly, BP reduction is attributed to improved dietary quality, rather than being solely linked to changes in the Na+/K+ ratio. Conclusion Salt-focused programs are effective public health tools mainly in managing individuals at high risk of hypertension. Nevertheless, in general, empowerment-based approaches are important strategies for lowering BP, by promoting health literacy that culminates in adherence to the Mediterranean diet and weight reduction.